JMJD3 regulate H3K27me3 modification via interacting directly with TET1 to affect spermatogonia self-renewal and proliferation - Jin Wang; Lingling Liu; Zebin Li; Haoyu Wang; Yuanyuan Ren; Kaisheng Wang; Yang Liu; Xinjie Tao; Liming Zheng (BMC Genomics, 2024)
Abstract Background In epigenetic modification, histone modification and DNA methylation coordinate the regulation of spermatogonium. Not only can methylcytosine dioxygenase 1 (TET1) function as a DNA demethylase, converting 5-methylcytosine to 5-hydroxymethylcytosine, it can also form complexes with other proteins to regulate gene expression. H3K27me3, one of the common histone modifications, is involved in the regulation of stem cell maintenance and tumorigenesis by inhibiting gene transcription. Methods we examined JMJD3 at both mRNA and protein levels and performed Chip-seq sequencing of H3K27me3 in TET1 overexpressing cells to search for target genes and signaling pathways of its action. Results This study has found that JMJD3 plays a leading role in spermatogonia self-renewal and proliferation: at one extreme, the expression of the self-renewal gene GFRA1 and the proliferation-promoting gene PCNA was upregulated following the overexpression of JMJD3 in spermatogonia; at the other end of the spectrum, the expression of differentiation-promoting gene DAZL was down-regulated. Furthermore, the fact that TET1 and JMJD3 can form a protein complex to interact with H3K27me3 has also been fully proven. Then, through analyzing the sequencing results of CHIP-Seq, we found that TET1 targeted Pramel3 when it interacted with H3K27me3. Besides, TET1 overexpression not only reduced H3K27me3 deposition at Pramel3, but promoted its transcriptional activation as well, and the up-regulation of Pramel3 expression was verified in JMJD3-overexpressing spermatogonia. Conclusion In summary, our study identified a novel link between TET1 and H3K27me3 and established a Tet1-JMJD3-H3K27me3-Pramel3 axis to regulate spermatogonia self-renewal and proliferation. Judging from the evidence offered above, we can safely conclude that this study provides new ideas for further research regarding the mechanism of spermatogenesis and spermatogenesis disorders on an apparent spectrum.